2014
DOI: 10.1371/journal.ppat.1004166
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Membrane-Bound Viral RNA Synthesis Reveals Potent Inhibition of Diverse Coronaviruses Including the Middle East Respiratory Syndrome Virus

Abstract: Coronaviruses raise serious concerns as emerging zoonotic viruses without specific antiviral drugs available. Here we screened a collection of 16671 diverse compounds for anti-human coronavirus 229E activity and identified an inhibitor, designated K22, that specifically targets membrane-bound coronaviral RNA synthesis. K22 exerts most potent antiviral activity after virus entry during an early step of the viral life cycle. Specifically, the formation of double membrane vesicles (DMVs), a hallmark of coronaviru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
162
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(171 citation statements)
references
References 75 publications
6
162
0
3
Order By: Relevance
“…2; Supplemental Table S2). Nsp6 is a membrane-spanning protein and is an integral component of the viral replication complex involved in double-membrane vesicle formation (Lundin et al 2014). Although the functional importance of these MERS-CoV variants in viral replication and their interaction with the host immune system remain to be elucidated, our data showed that the selection of these variants may not be independent from each other, suggesting the unit of selection may be a combination of variants rather than individual variants.…”
Section: Resultsmentioning
confidence: 99%
“…2; Supplemental Table S2). Nsp6 is a membrane-spanning protein and is an integral component of the viral replication complex involved in double-membrane vesicle formation (Lundin et al 2014). Although the functional importance of these MERS-CoV variants in viral replication and their interaction with the host immune system remain to be elucidated, our data showed that the selection of these variants may not be independent from each other, suggesting the unit of selection may be a combination of variants rather than individual variants.…”
Section: Resultsmentioning
confidence: 99%
“…To perform the qRT-PCR-based coronavirus yield assay, the materials were: HCoV-229E nucleoprotein-derived forward primer (5 0 -TTAGAGAGCGTGTTGAAGGTG-3 0 ); reverse primer (5 0 -GTTCTGAATTCTTGCGCCTAAC-3 0 ); probe (5 0 -6-FAM-TCTGGGTTG/ ZEN/CTGTTGATGGTGCTA-IBFQ-3 0 ; and a standardization plasmid with a 294-bp sequence of the HCoV-229E N-gene. As reference compound, the HCoV RNA synthesis inhibitor K22 [35] (from ChemDiv) was used.…”
Section: Coronavirus Experimentsmentioning
confidence: 99%
“…Promising treatment approaches currently emerging in the scientific literature (66) include the novel molecule K22, which targets viral replication without cellular toxicity (99). It targets viral MERS-CoV 3C protease (79) and the interface between the MERS-CoV receptor-binding domain (RBD) and the receptor by inhibiting the enzymatic function of dipeptidyl peptidase 4 (DPP4) (100).…”
Section: Therapeutic Optionsmentioning
confidence: 99%